A case of visceral leishmaniasis and pulmonary tuberculosis in a post-partum woman - Claudia Colomba; Lucia Adamoli; Marcello Trizzino; Lucia Siracusa; Silvia Bonura; Manlio Tolomeo; Massimo Cajozzo; Giovanni Maurizio Giammanco (International Journal of Infectious Diseases, 2015)
Visceral leishmaniasis due to Leishmania infantum is a vector-borne zoonotic disease transmitted by sand fly bites endemic in rural or periurban areas of the Mediterranean basin. Pregnancy is accompanied by changes in immune response, mainly a decrease in cellular immunity and a proportional increase in humoral immunity. These physiological events result in increased risk of infection by pathogens whose immunity is based on a T-helper 1 predominant response. We describe a case of visceral leishmaniasis and pulmonary tuberculosis diagnosed in a post-partum woman four days after delivery. The diagnosis of leishmaniasis should be considered in pregnant women with fever and haematologic abnormalities in endemic regions or if a history of exposure in endemic areas is reported.